NANOPARTÍCULAS DE ALBUMINA HUMANA CONTENDO APOCININA OBTIDAS POR NANO SPRAY DRYER PARA DIRECIONAMENTO CEREBRAL: AVALIAÇÃO DA ATIVIDADE ANTIOXIDANTE - RONIK, DÉBORA FERNANDA VERES (2014)
Several drugs widely used by pharmaceutical industry come from natural origin. Apocynin is a methoxy-catechol obtained from Picrorhiza kurroa, a plant natural from India mountains, and it is used for treatment of chronic joint decease inflammatory, atherosclerosis and it has neuroprotective action. Its main action mechanism is to prevent the formation of NADPH oxidase, which is an enzymatic complex involved in generation of reactive species of oxygen. These species when high concentrated cause instabily in the redox balance and as a result causing cellular damage. NADPH contained in brain region contributes to development of neuropathologies related to high concentration of reactive species. Furthermore, the blood-brain barrier which protects the brain tissue acts as a avoider of the transposition of the drug from blood to central nervous system, and it hampers the balance between oxidant and anti-oxidant agents. Nanotechnology is a multidisciplinary science which comprises the use of devices that allow the transportation and the enhanced carriage of drugs. Nanostructured systems with modified surface charges make easier the drug transposition to brain region. In the present study human albumin nanoparticles containing apocynin by nano spray dryer method and the surface modification thought polisorbate 80 surfactant incorporation. Physico-chemical characteristics have been analysed as well as its anti-oxidant activity on hypochlorous acid (HOCl) and the radical (ABTS•+). The nanoparticles physicochemical characterization had shown eficiency of drug encapsulation with variation between 28 and 60%, average diameters were reduced between 150 – 200 nm, low polydispersity index and alteration of surface charges. X- Ray and DSC assays had shown nanoparticles with amorphous character. The spectrometric analysis in infrared region indicated absence of intermolecular interation between drug and polymer. The apocynin antioxidant action assays with ABTS•+ and with HOCl indicated inhibition profile similar to free drug. The spray drier method had shown eficiency, with adequations and the nanostructured apocynin kept its biological activity when compared to free drug.